CREACIÓN DE LA RUTA TURÍSTICA PARA EL CANTÓN AGUARICO, PROVINCIA DE ORELLANA - Alvarado Pantoja, Yelsin Néstor (2018)
Tourism, as an economic activity, has been gaining more importance internationally, new tourist destinations have been developed, enabling more people to travel around the world in search of new places. Therefore, tourism is an activity that has achieved a great development on which millions of jobs depend, generating income and new currencies; as well as the implementation of infrastructure and the development of tourism plans and projects in each country. Ecuador is considered a mega diverse country is among the 17 countries with the highest biodiversity in the world is considered multi-ethnic and multicultural in addition to having an extraordinary natural and cultural wealth, it is important to note that thanks to the publicity of the tourist campaign undertaken by the government With the slogan of "Ecuador loves life" and "All You Need is Ecuador", it has been promoted worldwide. The project: Prepare a tourist route in the Aguarico Canton, Province of Orellana. Three objectives were proposed: The first objective called: Establish the tourist diagnosis for the route of the Canton Aguarico Province of Orellana, allowed to raise and investigate information through bibliographic research and field work of the urban and rural parishes of the Aguarico canton, necessary data that were systematized through the use of the following techniques: Carla Ricaurte's diagnostic sheet, inventory cards and hierarchy of tourist attractions prepared by the Ministry of Tourism, files prepared by the Ministry of Culture, the FODA matrix, based on the Plan of Development and Territorial Planning of the Provincial Government of Sucumbíos and of the Plan of Development and Territorial Planning of the Municipal GAD of the Aguarico Canton and some documents referring to the theme of the project. In the diagnosis, the following data was taken into account: Location, general data, limits, economic aspect, population, culture, representative flora and fauna, protected areas, education, tourist attractions, tourist facilities, basic services, roads, clothing, housing, handicrafts , gastronomy among other characteristics of each parish. In addition, the analysis and interpretation of 18 questions prepared and designed with different questions related to the theme were made, which were reflected in a survey answered by 384 people, represented by 26% of the inhabitants, 34% for domestic tourists and 40% for international tourists. For the second objective called: Design a tourist route for the Canton Aguarico Province of Orellana. , a map of the Tourist Route called "Yasuní Tesoro Verde" was drawn up, which took into account the following aspects: Mission, Vision, objective, brand, description of the brand, slogan, the route has three sub routes called as follows: Subruta Island of monkeys, Subruta pink dolphins, Subruta Typical costumes. Each of these has the itinerary, costs, tourist script and recommendations for the trip. The third objective called: Raising strategies for the promotion of the tourist route for the Aguarico canton of Orellana, in order to ensure that the route is recognized by locals and foreigners, promotion strategies were developed in the following manner. Creation of 5 the social network "Facebook", manufacture of information fences, elaboration of pictograms, totems, triptychs, souvenirs such as: t-shirts, hats, jars and key rings that bear the mark of the route, as well as the socialization of the route with the stakeholders involved who were invited, who have a clear idea of the contribution of the project contributing to the tourism and socio-economic development of the parishes, canton and province, strengthening the joint work so that tourism is the axis of sustainable development for the benefit of the population and thus eradicate poverty and undertake micro-projects with the help of governments in turn.